Long-term Outcome of Allogeneic Hematopoietic Stem Cell Transplantation From Unrelated Donor Using Tacrolimus/Sirolimus-based GvHD Prophylaxis: Impact of HLA Mismatch. Issue 5 (May 2020) - Al Malki, Monzr M.; Gendzekhadze, Ketevan; Yang, Dongyun; Mokhtari, Sally; Parker, Pablo; Karanes, Chatchada; Palmer, Joycelynne; Snyder, David; Forman, Stephen J.; Nademanee, Auayporn; Nakamura, Ryotaro
Abstract : Background: While tacrolimus and sirolimus (T/S)-based graft-versus-host disease (GvHD) prophylaxis has been effective in preventing acute GvHD post hematopoietic cell transplantation (HCT), its efficacy and long-term outcome in matched (MUD) and mismatched unrelated donor (mMUD) setting is not well defined. Methods: Herein, we evaluated a consecutive case-series of 482 patients who underwent unrelated donor HCT (2005–2013) with T/S-based GvHD prophylaxis. Results: With a median follow-up of 6.2 years (range = 2.4–11.3), the 5-year overall survival (OS) and relapse/progression-free survival were 47.5% (95% confidence interval [CI]: 43.0-52.0) and 43.6% (95% CI: 39.1-48.1), respectively; and the 5-year cumulative incidence of nonrelapse mortality (NRM) and relapse were 24.9%, and 31.5%, respectively. In this cohort, mMUD was associated with worse OS (39.0% versus 50.7% at 5 y; P = 0.034), primarily due to greater risk of NRM (33.5% versus 21.7%; P = 0.038). While rates of relapse, acute (II–IV or III–IV) or chronic GvHD (limited or extensive) were not different, death caused by chronic GvHD (20.8% versus 12.8%; P = 0.022) and infection (33.0% versus 18.1%; P < 0.01) were significantly greater in mMUD. In multivariable analysis, high-risk disease (hazard ratio [HR] = 2.21, 95% CI: 1.16-4.23; P < 0.01) and mMUD (HR = 1.55, 95% CI: 1.15-2.08; P = 0.004) were independent predictive factors for OS. Conclusions: T/S-based GvHD prophylaxis is an effective and acceptable GvHD prophylactic regimen. However, survival after mMUD remained poor, possibly related to the severity of chronic GvHD. Abstract : Supplemental Digital Content is available in the text.